Stability of the n-Dimensional Mixed-Type Additive and Quadratic Functional Equation in Non-Archimedean Normed Spaces - Yang-Hi Lee; Soon-Mo Jung; Themistocles M. Rassias (Abstract and Applied Analysis)
We will prove the stability of the functional equation 2f(∑i=1nxi)+∑1≤i,j≤n,i≠jf(xi-xj)=(n+1)∑i=1nf(xi)+(n-1)∑i=1nf(-xi) in non-Archimedean normed spaces.